(untitled) (INTEGRATION PROCEEDING, 2023)
Early marriage takes place in adolescent development. In the 21st century, the phenomenon of early marriage among women is still common in developing countries. The reason for getting married early is not only to avoid free sex, but also to worry about the mindset of being afraid of not getting a life partner. This incident certainly has an impact on the family’s self-esteem, thus forcing the family to marry off the couple even though in reality the couple does not yet have an age that does not meet the legal requirements for marriage. There are several negative impacts of early marriage in Indonesia, including 56 teenage girls experiencing Domestic Violence (KDRT) although not too often. The impact of early marriage is social, psychological and health. Nearly 80% of girls face Domestic Violence (KDRT) such as being beaten, slapped. This study is intended to analyze the correlation between public knowledge and the use of drugs for toothache in the working area of the Asam-Asam Public Health Center. This study uses an analytical survey with a Cross Sectional approach with a total sample of 92 respondents in the Terminal Health Center Work Area, on the Lulut River, RT. 08. From the results of data analysis using the chi-square test, the p value of 0.005 is less than the value of (0.05) so it can be concluded that the alternative hypothesis (Ha) is accepted. There is a relationship between age at marriage and the incidence of domestic violence (KDRT) in women in the working area of the terminal health center, the value is obtained (p = 0.005 <0.05).